Adsorption of As(III) on porous hematite synthesized from goethite concentrate. (February 2017) - Yang, Xuetong; Xia, Ling; Li, Jialei; Dai, Min; Yang, Guangcheng; Song, Shaoxian
Abstract: Arsenite (As(III)) is toxic in drinking water, which becomes an environmental concern worldwide. This work was to synthesize porous hematite through the calcination of natural goethite concentrate for As(III) adsorption, including adsorption kinetics, isotherms and the influence of pH and temperature. The calcination was performed at 300 °C for 180 min, producing porous hematite with large amount of micropores. The maximum adsorption capacity of As(III) on porous hematite was achieved at pH 6.0 and 25 °C, about 14.46 mg g −1, compared with 2.965 mg g −1 on the original goethite concentrate. The improvement might be attributed to the formation of micropores and thus the increase in the surface area. Also, it was found that the adsorption was strongly pH dependent and reduced with increasing temperature. It is indicated that the low-cost porous hematite has great potential in As(III) removal from contaminated water. Highlights: Porous hematite was developed for As(III) adsorption by calcinating goethite. Porous hematite showed a higher adsorption capacity for As(III) than that for As(V). Porous hematite is a low-cost and effective adsorbent for As(III) removal.